Genetic analysis of yield and yield component traits in exotic soybean germplasm (Glycine max (L.) Merrill) for vegetable type under Indian Conditions: Genetic analysis of yield and yield component traits in exotic soybean germplasm (Glycine max (L.) Merrill) for vegetable type under Indian Conditions - VANGALA RAJESH,; SANJAY GUPTA,; GIRIRAJ KUMAWAT,; NEHA PANDEY,; SUBHASH CHANDRA,; V NATARAJ,; M SHIVAKUMAR,; G K SATPUTE,; LOKESH KUMAR MEENA,; SANJEEV KUMAR,; RACHANA TRIPATHI,; NISHA AGRAWAL, (Journal of Oilseeds Research, 2023)
The present investigation was carried out at ICAR-Indian Institute of Soybean Research, Indore during kharif, 2019 to evaluate 105 soybean germplasm accessions received from World Vegetable center (AVRDC), Taiwan for vegetable type under Indian Conditions. Genetic parameters such as genetic variability, heritability and genetic advance were estimated for 11 quantitative characters. High estimates of PCV and GCV were recorded for row yield, grain yield per plant, number of primary branches per plant, 100 seed weight, number of pods per plant, number of pod clusters per plant and plant height. This indicates considerable variability and provide scope for genetic improvement through selection. High heritability coupled with high genetic advance as percent of mean was found for row yield, grain yield per plant, 100 seed weight, and number of pods per plant, plant height and days to 50 per cent flowering. This designates careful selection leads to improvement of traits and provides better opportunities for selecting plant material for these traits in soybean breeding program for vegetable type.